2023
DOI: 10.3390/plants12213664
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics of Southern European Taxa in the Ranunculus auricomus Species Complex: The Apple Doesn’t Fall Far from the Tree

John Paul Bradican,
Salvatore Tomasello,
Francesco Boscutti
et al.

Abstract: The taxonomic status of many Southern European taxa of the Ranunculus auricomus complex remains uncertain despite this region’s proximity to the native ranges of the sexual progenitor species of the complex. We investigated whether additional sexual progenitor species are present in the Mediterranean region. Utilizing target enrichment of 736 single-copy nuclear gene regions and flow cytometry, we analyzed phylogenomic relationships, the ploidy level, and the reproductive mode in representatives of 16 populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 61 publications
4
22
0
Order By: Relevance
“…This is commonly achieved in target-capture data through HybPhaser (Nauheimer et al 2021), and has been shown to be highly effective in cases of neoallopolyploidy (e.g. Bloesch et al 2022;Bradican et al 2023); however the method requires careful selection of the presence of diploid references for putative parental clades, and is often unsuitable for groups with complex or ancient reticulation (e.g. McLay et al 2023).…”
Section: Reticulationmentioning
confidence: 99%
“…This is commonly achieved in target-capture data through HybPhaser (Nauheimer et al 2021), and has been shown to be highly effective in cases of neoallopolyploidy (e.g. Bloesch et al 2022;Bradican et al 2023); however the method requires careful selection of the presence of diploid references for putative parental clades, and is often unsuitable for groups with complex or ancient reticulation (e.g. McLay et al 2023).…”
Section: Reticulationmentioning
confidence: 99%
“…Furthermore, we incorporate studies of groups of dwarfed and robust forms from boreal Fennoscandia subjected to artificial cold and temperate climate regimes, recording the morphological traits in order to examine the phenotypic plasticity in response to climate. As previous studies would seem to indicate that sexual reproduction is rare in populations present at the margins of this group's range, we examine whether this extends to Northern Europe where the populations are typically less isolated and more numerous than those in Southern Europe (Ericsson, 2001;Bradican et al, 2023). Although phenotype has previously been the basis for the classification of many of the taxa in this species complex, more recent research has demonstrated in multiple cases that the morphological taxa are often polyphyletic when sequence data are taken into consideration (George et al, 2014;Bradican et al, 2023;Hodacě t al., 2023).…”
Section: Introductionmentioning
confidence: 98%
“…As previous studies would seem to indicate that sexual reproduction is rare in populations present at the margins of this group's range, we examine whether this extends to Northern Europe where the populations are typically less isolated and more numerous than those in Southern Europe (Ericsson, 2001;Bradican et al, 2023). Although phenotype has previously been the basis for the classification of many of the taxa in this species complex, more recent research has demonstrated in multiple cases that the morphological taxa are often polyphyletic when sequence data are taken into consideration (George et al, 2014;Bradican et al, 2023;Hodacě t al., 2023). To date, it is unclear whether the relatively widespread R. monophyllus morphogroup represents a distinct lineage, as opposed to the many mosaic-like hybrid networks typical of this group (Karbstein et al, 2022).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations